(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Morning report (MR) is an important daily activity in the department of internal medicine and it is the most important educational activity in the residency training program. Same is true for any hospital that tends to promote their service through continuous medical education(CME). There is increasing demand to practice medicine which is evidencebased and medical education is no exception. Evidencebased, self-directed, learner-centered education proven to be more effective method of learning than the traditional method for the medical residents and thereby more and more emphasis placed on such curricula in postgraduate medical education. The current standing on this issue reviewed to increase our awareness and improvement of MR in the era of Evidence-Based Medicine(EBM). DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11410 J Bangladesh Coll Phys Surg 2012; 30: 91-95